The Legal Nature of Cybercrime - Yourmeche , Mourad (Journal of Legal Studies and Researches, 2025)
Cybercrime is considered one of the most dangerous crimes witnessed by the modern world. Its seriousness lies in its special nature and distinctive characteristics, as it differs from traditional crimes that occur in the physical world. Cybercrime is the type of crime that takes place in cyberspace, also known as the virtual world, represented by the internet and its electronic components. Therefore, it is closely linked to the World Wide Web, which in turn complicates matters and makes it more challenging for the authorities responsible for combating and addressing this type of crime, whether at the level of security agencies or judicial bodies.